1999
DOI: 10.1021/ol990614c
|View full text |Cite
|
Sign up to set email alerts
|

A New Transformation of Silanols. Palladium-Catalyzed Cross-Coupling with Organic Halides in the Presence of Silver(I) Oxide

Abstract: The reactions of aryl- and alkenylsilanols with organic halides are found to proceed in a catalyst system of 5 mol % of Pd(PPh3)4 and Ag2O (1 equiv) to give the corresponding coupling products in up to 84% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(55 citation statements)
references
References 10 publications
1
52
0
2
Order By: Relevance
“…C À C bond formation by Hiyama cross-coupling with an iodoarene using silver(I) oxide as an activator afforded para-terphenyl derivative 5. [16,17] Modification of the allyl group under Heck arylation conditions in the presence of TBAF afforded desilylprotonated styrene derivative 6. [a] Allylsilane (10 equiv) was used.…”
Section: Single C à F Bond Cleavage Of Trifluoromethylarenes With An mentioning
confidence: 99%
“…C À C bond formation by Hiyama cross-coupling with an iodoarene using silver(I) oxide as an activator afforded para-terphenyl derivative 5. [16,17] Modification of the allyl group under Heck arylation conditions in the presence of TBAF afforded desilylprotonated styrene derivative 6. [a] Allylsilane (10 equiv) was used.…”
Section: Single C à F Bond Cleavage Of Trifluoromethylarenes With An mentioning
confidence: 99%
“…[20] Later, arylsilanols, [21] trialkoxy(aryl)-silanes, [22] poly(phenylsiloxane)s, [23] aryl(halo)silacyclobutanes, [24] arylsilatranes, [25] and triethylammonium arylbis(catecholato)silicates [26] were used for the crosscoupling with aryl halides and triflates.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the best activator was found to be silver (I) oxide, which promoted the coupling of aryl silanol 6 to a variety of aryl iodides (Chart 2). 17,18) The common silicon coupling promoter, tetrabutylammonium fluoride (TBAF), was ineffective in this method. Alkenylsilanols were also employed with similar success.…”
Section: Organosilanol Cross-couplingmentioning
confidence: 99%